Analisis Transformasi Digital Terhadap Pengelolaan Keuangan UKM Di Masa Pandemi Covid 19 - Suginam Suginam (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The purpose of this research is to test the analysis of the success of digital transformation in the financial management of SMEs during the covid 19 pandemic. The research method uses a quantitative method approach and performs an analysis using multiple linear regression. The data is taken from SMEs and processed using SPSS. The results of the research show that the variables of Realization of Sustainable Business Value (X1), Market Accepted Innovation (X2) and Cloud / Digital-Based Business Process Improvement (X3) have an influence on the success of digital transformation where it can be seen the acceptance of H1, H2 and H3. In addition, all variables have a joint influence (Stimulant) on the success of the digitalization transformation and is supported by the acceptance of H4.